Occult nodal metastases in T1-T2cN0 oral squamous cell carcinoma: Correlation between sentinel node positivity and completion neck dissection analysis. (April 2023) - Guerlain, J.; Marhic, A.; Casiraghi, O.; Lumbroso, J.; Garcia, G.; Breuskin, I.; Janot, F.; Temam, S.; Gorphe, P.; Moya-Plana, A.
Highlights: SN is a safe and effective procedure for managing T1/T2 cN0 OSCC. In 80% of cases, only SN were positive and neck dissection could be avoided. The SN micrometastatic involvement is associated with only one positive SN. Abstract: Objectives: Sentinel node procedure (SN) is a standard procedure that has shown its safety and effectiveness for T1/T2 cN0 oral squamous cell carcinoma (OSCC), with completion neck dissection (CND) for patients with positive SN. The aim of this study was to characterize the nodal involvement in a cohort of SN + OSCC. Materials and Methods: Patients with T1/T2 cN0 OSCC with positive SN with CND were included in this single-center, prospective cohort study between 2000 and 2013. Results: 54/301 patients had at least one positive SN. In 43/54 (80 %) cases, only the SN(s) were invaded; with only one SN involved (SN+=1) in 36/54 (67 %) cases. No predictive factors of nodal involvement in the CND were found considering the followings: SN micro/macrometastases, primary tumor's depth of invasion (DOI), perineural spread, lymphovascular involvement, primary tumor location, T stage and extranodal extension. The SN micrometastatic involvement (n = 22) was significantly associated with only one SN + CND- (p = 0.017). In the group of patients with unique micrometastatic involvement in the SN (n = 20/54), there was a higher isolated nodal recurrence free time (p = 0.017). Conclusion: 80% of T1/T2 cN0 OSCC with positive SN had no other lymph node metastases in the CND, questioning the potential benefits of this procedure. Predictive factors such as the size of the SN metastasis need to be tested to stratify the risk of positive non-SN lymph nodes leading to a personalized treatment, lowering the therapeutic morbidity while maintaining the oncologic safety.